Psychological factors of language learning - azi, naima (El Omda in Linguistics and Discourse Analysis, 2025)
Talking about the concept of learning actually focuses on two important axes: The first is to talk about learning in general, for example in terms of its conditions of motivation, maturity, and practice. The second is to talk about language learning. It is certain that linguistic learning has a set of characteristics that distinguish it from other types of learning, and this is what we will discuss during this study. Through this research, we aim to reveal the most important psychological foundations of linguistic learning, the knowledge of which contributes to improving the educational process, whether for the first language or the second language.